Avulsion of the Levator Ani at First Pregnancy - Khusen, Denny (Indonesian Journal of Obstetrics and Gynecology, 2013)
Objective: To investigate whether demographic and obstetric risk factors are associated with avulsion of the levator ani at first pregnancy. Methods: A series of case was undertaken on 4 pregnant nulliparous women seen with a gestational age of more than 37 weeks. We analyzed with 3D/4D translabial ultrasound and digital assessment data of 4 women seen in a tertiary Urogynecological clinic. The use of 3D/4D ultrasound as a means of detection of trauma to the levator ani. Result: We had 4 women who had levator ani avulsion. Diagnosis of levator trauma (avulsion) on tomographic ultrasound was correlated with predelivery demographic variables and ultrasound parameters. Conclusion: With a greater understanding on the function of pelvic floor muscles, risk factors for trauma and damage as a result of pregnancy and birth, healthcare professionals will have better ability to meet the needs of women in the childbearing year. This study utilized a scoring system that can be used to predict the occurrence of levator ani muscle damage. In the end, the decline in quality of life for women, especially after a birth, can be prevented. [Indones J Obstet Gynecol 2013; 37-1: 51-6] Keywords: 3D/4D translabial ultrasound, demographic, levator ani avulsion, obstetric risk factors